International Multiconference Information Society - Gams, Matjaž (Informatica, 2025)
The “Information Society” Multiconference is a multifaceted event that brings together diverse research disciplines, promotes topics ranging from AI to ethics, and provides an excellent opportunity for networking and open-access publication. Each year, it attracts both domestic and international researchers, enriching the dialogue with a global perspective.